Preparation of KOH-Modified Rice Husk Char via Heat Treatment for Effective Removal of Pb2+ - Shah Rukh Khan; Ali Khan; Asif Ali; Yoshiro Tahara; Michiaki Matsumoto (Journal of Chemical Engineering of Japan)
In this study, a thermal modification method was used to convert rice husk to rice husk char (RHC), and then the RHC was treated with KOH to produce KOH-modified RHC (KMRHC). KMRHC showed remarkable efficacy for the removal of Pb2+ from aqueous media. The experimental factors that affect Pb2+ adsorption were investigated. At pH 6 and 303 K, KMRHC could remove 119 mg/g of Pb2+ from aqueous solution at an adsorbent dosage of 2 g/L. The Pb2+ adsorption efficiency was determined to be 95.9% under the optimized conditions. Thermodynamic analyses revealed that Pb2+ adsorption to KMRHC is an exothermic and spontaneous process. According to kinetic tests, the adsorption of Pb2+ more closely followed a pseudo-second-order model than a pseudo-first-order model. KMRHC showed a larger adsorption capacity and faster adsorption kinetics for Pb2+ adsorption than previously reported RHCs.